Norepinephrine infusion increases urine output in children under sedative and analgesic infusion - Piva,Jefferson (2014)
Objective: to evaluate the effects of early norepinephrine (NE) infusion in children submitted to mechanical ventilation (MV) requiring continuous sedative and analgesic infusion. Methods: double-blinded, randomized, placebo-controlled trial enrolling children (1 month to 12 years of age) admitted to a Brazilian PICU and expected to require MV and continuous sedative and analgesic drug infusions for at least five days. Children were randomized to receive either norepinephrine (NE) (0.15 mcg/kg/min) or normal saline infusion, started in the first 24 hours of MV, and maintained for 72 hours. We compared hemodynamic variables, fluid intake, renal function and urine output between groups. Results: forty children were equally allocated to the NE or placebo groups, with no differences in baseline characteristics, laboratorial findings, PRISM II score, length of MV, or mortality between groups. The average norepinephrine infusion was 0.143 mcg/kg/min. The NE group showed higher urine output (p = 0.016) and continuous increment in the mean arterial pressure compared to the baseline (p = 0.043). There were no differences in the remaining hemodynamic variables, fluid requirements, or furosemide administration. Conclusion: early norepinephrine infusion in children submitted to MV improves mean arterial pressure and increases urine output. These effects were attributed to reversion of vasoplegia induced by the sedative and analgesic drugs.